Bioavailability of nutrients and harmful elements in ash fertilizers: Effect of granulation. (May 2017) - Pesonen, Janne; Kuokkanen, Toivo; Rautio, Pasi; Lassi, Ulla
Abstract: Environmental policies of the European Union (EU) aim to increase the amount of renewable energy and to improve the use of waste streams. This will increase the amount of fly ash (FA) from biomass combustion, thereby increasing the need for its utilization. Biomass FA is a good fertilizer since it contains most of the nutrients that plants need. Sequential leaching would provide a more accurate assessment of the potential bioavailability of the harmful elements and nutrients than the pseudo-total and/or water-soluble concentration analysis that EU environmental legislation typically requires. This study investigated the effect of granulation and ammonium sulfate addition on the solubility and bioavailability of nutrients and harmful elements from peat and wood co-combustion FA by using sequential leaching and pseudo-total acid digestion. The recoveries of the easily bioavailable nutrients Ca, K, Mg, P, and S as well as the total bioavailability of Ca, K, Mg, and S reduced significantly after granulation. Therefore, granulation reduced the fertilizing effect of FA. The pseudo-total recovery of Ca, Mg, and S reduced after granulation, indicating that these types of FA form some very stable silicate compounds besides the common self-hardening products. Ammonium sulfate addition increased the recoveries of the easily bioavailable nutrients and total bioavailability recoveries of the Ca, K, and Mg back to the same levels as those in FA. The total bioavailability of the harmful elements As, Cd, Cr, Cu, Ni, Pb, and Zn was very low, and this does not limit the usability of FA as a fertilizer. Highlights: Effect of granulation on the bioavailability of many elements from ash was studied. Granulation reduced the bioavailabilities of the nutrients significantly. Bioavailabilities of the harmful elements were very low.